2013
DOI: 10.4209/aaqr.2012.08.0225
|View full text |Cite
|
Sign up to set email alerts
|

Ship-Borne Measurements of Columnar and Surface Aerosol Loading over the Bay of Bengal during W-ICARB Campaign: Role of Airmass Transport, Latitudinal and Longitudinal Gradients

Abstract: The present study analyzes simultaneous and collocated measurements of spectral columnar aerosol optical depth (AOD) and the variations in total mass concentration of near surface aerosols in the marine atmosphere over the Bay of Bengal (BoB) during the winter phase of the Integrated Campaign for Aerosols, gases and Radiation Budget (W-ICARB) expedition of December and January 2008/2009 on board the Oceanographic Research Vessel (ORV) of Sagar Kanya. High AOD 500 values (> 0.8) are found close to coastal regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The backward trajectories terminating over Pune on 21 and 28 November 2010 originate over the Bay of Bengal (BoB) and traverse through Indian landmass located to the southeast of Pune. Studies based on measurements over the BoB indicate that atmospheric aerosol loading over the BoB is influenced by anthropogenic emission over eastern and southern India along with biomass burning in Burma (Kumar et al 2013;Kumar et al 2015). In addition to it, the MODIS fire counts during post-monsoon season as depicted in Fig.…”
Section: Oc/ec Ratio and Source Characteristicsmentioning
confidence: 98%
“…The backward trajectories terminating over Pune on 21 and 28 November 2010 originate over the Bay of Bengal (BoB) and traverse through Indian landmass located to the southeast of Pune. Studies based on measurements over the BoB indicate that atmospheric aerosol loading over the BoB is influenced by anthropogenic emission over eastern and southern India along with biomass burning in Burma (Kumar et al 2013;Kumar et al 2015). In addition to it, the MODIS fire counts during post-monsoon season as depicted in Fig.…”
Section: Oc/ec Ratio and Source Characteristicsmentioning
confidence: 98%
“…Results clearly show that a sharp decline in both AOT and PM2.5 values is observed during the first week of lockdown; however after some time, (during the last week of DLP-2020) a sudden increment in both the parameters is noticed attributed to the end of lockdown phase and the regain in anthropogenic activities associated with the restoration of social and commercial pursuits and increase in temperature (Sachin et al, 2020;Yueling et al, 2020). Since, relative humidity (RH) plays an effective role in the hygroscopic growth of atmospheric pollutants (Carrico et al, 2003;Kumar et al, 2013;Ahlawat et al, 2020).…”
Section: Role Of Meteorologymentioning
confidence: 99%
“…Detailed studies have been carried out regarding the heterogeneity of aerosols and aerosol loading over the BoB for different seasons (Moorthy et al 2003(Moorthy et al , 2008(Moorthy et al , 2010Kumar et al 2011Kumar et al , 2013. During the W-ICARB (Winter Integrated Campaign for Aerosols, Gases and Radiation Budget) field experiment during December 2008 and January 2009, it was found that there was an abundance of fine mode aerosols (highly absorbing), mostly of anthropogenic origins from the nearby continents (Moorthy et al 2010;Kaskaoutis et al 2011;Kumar et al 2013). These aerosols are mainly confined to the boundary layer (BL) due to the sources being near.…”
Section: Introductionmentioning
confidence: 99%